Coastal management : global challenges and innovations - Krishnamurthy, R. R.; Jonathan, M.P.; Srinivasalu, Seshachalam; Glaeser, Bernhard (London : Academic Press, 2019)
"Coastal Management: Global Challenges and Innovations focuses on the resulting problems faced by coastal areas in developing countries with a goal of helping create updated management and tactical approaches for researchers, field practitioners, planners and policymakers. This book gathers, compiles and interprets recent developments, starting from paleo-coastal climatic conditions, to current climatic conditions that influence coastal resources. Chapters included cover almost all aspects of coastal area management, including sustainability, coastal communities, hazards, ocean currents and environmental monitoring. Contains contributions from a global pool of authors with a wide range of backgrounds and disciplines, making this an authoritative and compelling reference presents the appropriate tools used in monitoring and controlling coastal management, including innovative approaches towards community participation and the implementation of tactics includes case studies from across the world, allowing for a thorough comparison of situations in both developing and developed countries"--
Includes bibliographical references and index.
Keywords: Coastal zone management -- Developing countries